2008 IEEE International Conference on Robotics and Automation 2008
DOI: 10.1109/robot.2008.4543642
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory robot control for a partially observable environment using episodic memories

Abstract: This paper explains an episodic-memory based approach for computing anticipatory robot behavior in a partially observable environment. Inspired by biological findings on the mammalian hippocampus, here, the episodic memories retain a sequence of experienced observation, behavior, and reward. Incorporating multiple machine learning methods, this approach attempts to help reducing the computational burden of the partially observable Markov decision process (POMDP). In particular, the proposed computational reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In one experimental study two robots had the goal of exchanging places while navigating through an area with or without obstacles [8]. In another study, an episodic memory-based approach was proposed for computing anticipatory robot behavior in a partially observable environment, and the results of a robot navigation experiment were presented [9].…”
Section: Related Workmentioning
confidence: 99%
“…In one experimental study two robots had the goal of exchanging places while navigating through an area with or without obstacles [8]. In another study, an episodic memory-based approach was proposed for computing anticipatory robot behavior in a partially observable environment, and the results of a robot navigation experiment were presented [9].…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, for robots, the premise here is that experience does matter as well. 8 We argue that the learned experience can be integrated with the cognitive map to enable robot perceive and navigate freely in an environment. It is thus natural to seek inspiration in human experience in order to achieve their adaptivity and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study was reported previously [6] in which two robots had the goal of exchanging places while navigating through an area with or without obstacles. In another study [7], the author proposed an episodic-memory-based approach for computing anticipatory robot behavior in a partially observable environment, and presented the results of a robotnavigation experiment.…”
Section: Introductionmentioning
confidence: 99%